Microstructure and mechanical properties of a polyethylene/polydimethylsiloxane composite prepared using supercritical carbon dioxide. Issue 5 (22nd May 2012) - Zhu, Rui; Hoshi, Toru; Muroga, Yoshio; Hagiwara, Toshiki; Yano, Shoichiro; Sawaguchi, Takashi
Abstract A polymer composite of polyethylene (PE) and polydimethylsiloxane (PDMS) was prepared using supercritical carbon dioxide despite the two polymers usually being immiscible and possessing a phase‐separated morphology. This article reports in detail the preparation, microstructure, crystallinity, and mechanical properties of the resulting PE/PDMS composite. The formation mechanism of the PE/PDMS composite consisted of supercritical impregnation of an octamethylcyclotetrasiloxane (D4) monomer and an initiator into a PE substrate followed by in situ polymerization within the substrate. Differential scanning calorimetry, wide‐angle X‐ray diffraction, and small‐angle X‐ray scattering measurements showed that PE and PDMS were blended at the nanometer level. The PDMS generated in the amorphous region of PE did not affect its crystallinity. Dynamic viscoelastic analyses and tensile tests were used to measure the mechanical properties of the composites including storage and Young's modulus, fracture stress, and strain. These properties were found to depend on the composition of the composite. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013